Efficacy of flurbiprofen 8.75 mg delivered as a spray or lozenge in patients with sore throat due to upper respiratory tract infection: a randomized, non-inferiority trial in the Russian Federation - Radkova, Eugenia (J Pain Res, 2017)
OBJECTIVE: To assess the efficacy of flurbiprofen 8.75 mg delivered as a spray or lozenge in patients with sore throat due to upper respiratory tract infection (URTI). MATERIALS AND METHODS: This multicenter, double-blind, double-dummy, non-inferiority study randomized 440 adults with recent-onset, moderate-to-severe sore throat due to URTI to a single dose of either flurbiprofen 8.75 mg spray (n=218) or flurbiprofen 8.75 mg lozenge (n=222). The presence or absence of beta-hemolytic streptococci (A or C) was confirmed by culture tests (throat swab). The primary efficacy end point was the difference from baseline to 2 hours post-dose in sore throat pain intensity scale (STPIS pain intensity difference [PID] 2h), a validated 100 mm visual analog scale (from 0=“no pain” to 100=“severe pain”), with a non-inferiority margin of −6 mm. Secondary end points included STPIS PID at 1 hour (STPIS PID 1h) and over 2 hours (STPIS sum of sore throat pain intensity differences [SPID](0–2h)) and ratings of patient satisfaction and investigator assessment of drug efficacy at 2 hours. Safety (adverse events [AEs]) was also assessed. RESULTS: Reductions in sore throat pain intensity at 2 hours (STPIS PID 2h) were similar for spray (least square mean −40.51) and lozenge (−40.10) (difference: 0.41, 95% confidence interval [95% CI] −3.20, 4.01), with non-inferiority demonstrated. Subgroup analyses showed similar efficacy (STPIS PID 2h) for patients testing positive or negative for Strep A or C. There was no significant difference between spray and lozenge in STPIS PID 1h or STPIS SPID(0–2h), and patient satisfaction and investigators’ assessment of efficacy at 2 hours were similar for both groups. There were no significant differences in AEs between the two groups, with 17 drug-related events across both groups, all being mild and none being serious. CONCLUSION: Both formulations demonstrated comparable efficacy and safety profiles and provide patients with two different treatment formats to choose from for effective symptomatic relief of sore throat, depending on their preference.